Raising your arms towards branding: how Narta found its place in a mature market - Gonçalinho, David José do Carmo Chalbert Cardeira (2018)
The main purpose of this project is to understand how a brand can differentiate itself in a mature market, having as key drivers the Brand Experience and Brand Communication Management. In this case, these conceptual models will be applied to Garnier’s deodorant brand – Narta. Narta is a ten years old brand in Portugal of deodorants, sold in the mass-market circuit and with a flat performance in the last years. "What people really desire are not products but satisfying experiences" (Abbot, 1955). This quote highlights the increasing importance of experiencing a brand and how it can lead to a powerful and unique differentiation strategy. Regarding Brand Experience dimension, the constructs of parity and similarity will be analyzed and, in order to provide a strong differentiation, the Isomorphic Change Model will help us to guide the management of external and internal pressures that pushes into similarity and parity. At last, a brief look at the Herzberg’s motivational theory will be performed in order to fully understand the positive impact of a brand differentiation in the consumers’ satisfaction/dissatisfaction dichotomy. Communicating such difference will make a brand valuable and considered when the purchase act occurs. Matching the importance of the consumer journey with an Integrated Marketing Communication plan, Narta will be able to communicate its new positioning and enhance its performance. This study will not only take in consideration market insights from Nielsen but also shopper and consumer insights in both quantitative and qualitative ways from independent agencies. These studies will help to establish a proper conclusion about the brand’s perception and the brand’s competitiveness when comparing with other deodorants brands in Portugal. Hence, this project aims to diagnose the reason beyond the flat performance of Narta and implement a new positioning, expressed with the proper Marketing Communication Plan. Matching the theory with the reality of daily business will lead to a positive impact on Narta’s performance in the deodorant market, helping the brand to reach its fair position in awareness and image fields while leveraging its sales in this competitive and mature but huge market.